Características psicológicas, faciais e buco-dentárias de crianças com bruxismo da clínica de odontopediatria da Faculdade de Odontologia Araçatuba - Unesp - Santos, Fernanda Alves [UNESP] (2014)
The purpose of this research was to evaluate the psychological, facial and dental characteristics of children 4-10 years of age with bruxism. All children were evaluated by interview and clinical examination to determine the presence of parafunction. They were divided into three groups according to age. The projective test HTP to the children and also an interview with the parents as a form of psychological analysis in the initial period and after 18 months was applied. The orthodontic analysis verified the facial pattern, the Angle classification, previous sagittal relationship, overjet and overbite, cross-evaluation. The pediatric dental analysis consisted of an oral examination and a questionnaire found that the following variables: age, sex, history of bruxism, child behavior, general health status and oral habits. The results were analyzed using the qualitative and quantitative aspects and have been described in the table and graphs.Of the 460 children, 68 had the habit of bruxism (15%), 38 females and 30 males. Most of children belonged to the age group 4-6 years (43%). The HTP test showed that 58% and 73% of children showed bruxism traits of insecurity, shyness and inadequacy in the first period and after 18 months, respectively. The questionnaire administered to the parents showed that anxiety in children occurred in 56% and 49%, respectively, in both periods. The orthodontic analysis revealed that 60% of bruxism children had skeletal pattern I and 48% with Class I malocclusion. Normal sagittal relationship with 97% and overjet in 47%. Only 9% of the children showed vertical relationship with posterior cross-bite. The frequency of nocturnal bruxism was 96%, with restless sleep in 72% and 62% with agitated behavior. Among the general health problems, 40% with a history of allergic rhinitis. Occurrence of bruxism in other family members...